Penerapan Teknik Kognitif Behavioral Untuk Mengurangi Kecanduan Gadget Pada Siswa Kelas IX di MTs Negeri 1 Sumenep - dewi fatimah (STKIP PGRI SUMENEP, 2023)
Gadget is another term for mobile phones or smartphones. Nowadays, almost everyone uses gadgets in their daily life. However, the use of gadgets has many impacts on users, both negative and positive impacts. This study aims to analyze the causes of gadget addiction in students and to help students to be able to overcome the problems they experience and problems that will come. The population of this study were all students of class IX MTsN 1 Sumenep, while the sample was students of class IX who were taken randomly using the Proportional Random Sampling Technique with a total of 10 students. The results showed that gadget addiction in students can be caused by many factors, for example students think too much about gadgets, students cannot control themselves when using gadgets, students often feel anxious when not using gadgets, and many other influences. The application of cognitive behavioral techniques is very appropriate for students who are addicted to gadgets.